The Impact of COVID-19 Infection on Patients with Chronic Diseases Admitted to ICU: a Cohort Retrospective Study - Farah Alammari; Batla S. Al-Sowayan; Bayan Albdah; Arwa A. Alsubait (Springer, 2023)
Abstract The coronavirus disease (COVID-19) infection is causing significant morbidity and mortality rates worldwide. A comprehensive investigation of the disease characteristics, especially among vulnerable disease groups, could help better manage the disease and reduce the pathogen's effect. This retrospective study examined the impact of COVID-19 infection on three groups of patients with chronic diseases. We investigated the clinical characteristics and outcomes of 535 COVID-19 patients with cardiovascular diseases (CVD), chronic kidney diseases (CKD), and Cancer that were admitted to the Intensive Care Unit (ICU). Of the total cases, 433 patients (80.93%) were discharged from the ICU, and 102 patients (19.06%) were declared dead. Patients' symptoms, their clinical laboratory findings, number and type of medications, length of ICU stay, and outcome were collected and analyzed. Most COVID-19 patients included in our study were associated with other comorbidities such as diabetes mellitus, hypertension, and heart disease and failure. Upon ICU admission, the main COVID-19-related symptoms in CVD, CKD, and cancer patients were cough (55.73, 50.42, and 50.5%, respectively), Shortness of Breath (SOB) (59.38, 43.1, and 43.7%, respectively), and fever (41.15%, 48.75%, and 28.2%, respectively). In terms of lab findings, D-dimer, LDH, and inflammatory markers, in particular, were outside the normal range. Treatment options for patients with COVID-19 in ICU were mainly antibiotics, synthetic glucocorticoids, and Low Molecular Weight Heparin (LMWH). Furthermore, CKD patients had a longer ICU stay (13.93 ± 15.87 days) which illustrates the poorer outcome in this group of patients compared with the others. In conclusion, our results highlighted the significant risk factors among COVID-19 patients within the three groups. This can guide physicians in prioritizing ICU admission and help in the management of critically ill patients with COVID-19.